Postanesthetic Cold Sensibility Test as an Indicator for the Efficacy of Inferior Alveolar Nerve Block in Patients with Symptomatic Irreversible Pulpitis of Mandibular Molars - Mohamed El Sayed; Kamis Gaballah (International Journal of Dentistry)
Aim of the Work. The goal of the current study was to investigate the capability of the cold test to predict the profound pulpal anesthesia before starting the endodontic treatment of mandibular first molars with symptomatic irreversible pulpitis (SIP). Materials and Methods. This study was conducted on the mandibular first molars of 54 patients (35 males and 19 females) with signs and symptoms of SIP. To anesthetize the affected molars, all patients received a single carpule of 2% lidocaine with 1 : 100000 epinephrine using a standardized inferior alveolar nerve block (IANB) technique. The cold test was conducted before beginning the endodontic procedures and after gaining lip numbness, and the results were reported as either positive or negative response. The root canal preparation (RCP) was then initiated and the patients’ responses were documented (Gold standard test). True pulpal anesthetic failure was described as a pain perception during the access cavity and pulp tissue removal. True pulpal anesthesia was defined as no pain or discomfort during the access cavity and pulp extirpation. The qualitative variables frequencies and percentages of patients with true/false positive and negative responses were determined and then compared using the Chi-square test. The pain perception of male and female patients during the cold test and gold standard was compared using the Fisher exact test. The following diagnostic parameters were calculated using an online statistical calculator: sensitivity, specificity, predictive values, accuracy, and Youden index. In addition, a receiver operating characteristic curve (ROC) was constructed and the area under the curve (AUC) was calculated. Results. The overall percentage of actual failure of pupal anesthesia was 57%. The sensitivity, specificity, positive predictive value, negative predictive value, accuracy, and Youden index for the cold test were 0.87, 0.91, 0.93, 0.84, 0.89, and 0.78, respectively. There was no statistically significant difference between male and female patients regarding their responses to cold testing and the gold standard test (P>0.05). Besides, the patients’ reactions to the cold test were significantly matched with their reactions to the gold standard test (P<0.05). The area under the ROC was mostly 0.9. Conclusion. The cold test could be a valuable and accurate method for predicting the potential pupal anesthesia before beginning the endodontic treatment of mandibular molars with symptomatic irreversible pulpitis, particularly after obtaining postanesthetic soft tissue numbness.